Community Service through the Literacy Village Model Reading Park in Tapak Gedung Village, Kepahiang Regency - Arono; Irma Diani; Wisma Yunita (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Local cultural literacy with character is currently lacking in society so that it does not describe and reflect the area where a region is located. This is because the low literacy culture of Indonesian society today has an impact on the low interest in reading and writing in society. This condition is also influenced by the limited number of reading parks or village libraries, which is only 3.06%. A different thing was found in Tapak Gedung which does not yet have a village library so that literacy activities in reading and writing there are still limited. For this reason, this community service activity aims to describe and reveal the tendency of the community's interest in reading and writing, train the community in writing in the community so that they can foster their interest in reading and writing, compile literacy drafts in identifying folk tales and poetry, and describe responses to reflections on activities that have been carried out to provide input and action on the literacy village model activities of the reading corner that has been carried out. The community service method used is Tabatage Unib (Tapak Gedung Reading Park, University of Bengkulu) APTE Model (Needs Analysis, Training, Action, and Evaluation). The community service team in this case uses this model as a stage of service. Literacy reading and writing that is developed, namely reading and telling stories and writing village history/potential local wisdom in the form of fiction. The community is more dominant in telling stories than reading and is no longer illiterate. The tendency of existing folklore is in the form of tourist attractions, myths, folklore, typonyms, history, and events in society. Training and guidance can maximize the APTE model independently and in groups that are actively followed by participants. There needs to be printed and non-printed reading materials with a good internet connection network. The output of community service activities is documented in the form of recordings published on YouTube and publication of articles in the Sinta 5 journal.